Possible role of IL-6 and TIE2 gene polymorphisms in predicting the initial high transport status in patients with peritoneal dialysis: an observational study. Issue 10 (26th October 2016) - Ding, Li; Shao, Xinghua; Cao, Liou; Fang, Wei; Yan, Hao; Huang, Jiaying; Gu, Aiping; Yu, Zanzhe; Qi, Chaojun; Chang, Xinbei; Ni, Zhaohui
Abstract : Objectives: The aim of this study was to investigate the effect of interleukin (IL)-6 and TIE2 gene polymorphisms on baseline peritoneal transport property. Design: An observational study. Setting: Renji Hospital in Shanghai, China. Participants: This study included 220 patients with continuous ambulatory peritoneal dialysis (PD). Outcome measures: Patients were divided into 2 groups based on the results of an initial peritoneal equilibration test performed within 3 months of starting PD therapy: group 1 consisted of low/low average transporters (n=123), and group 2 consisted of high/high average transporters (n=97). We genotyped TIE2 and IL-6 polymorphisms and analysed their effects on baseline transport status. Results: The genotype AT in IL-6 Rs13306435 and the genotype CC in TIE2 Rs639225 were both negatively associated with a higher initial peritoneal transport status (IL-6 Rs13306435: OR=0.408, 95% CI 0.227 to 0.736; TIE2 Rs639225: OR=0.188, 95% CI 0.044 to 0.806). Conclusions: IL-6 and TIE2 polymorphisms are associated with baseline peritoneal transport property.